White light emitting silicon nanocrystals as nanophosphor - Lee, S; Cho, WJ; Han, IK; Choi, WJ; Lee, JI (WILEY-V C H VERLAG GMBH, 2004)
We exploited the practical sonochemical route for preparing silicon nanocrystals at room temperature and ambient pressure. This synthesis provided the very fast reaction within a few hours and the useful modification for the surface of silicon nanoparticles. The average size of prepared nanocrystals was 2.8 nm and confirmed by TEM images. The chlorine-capped nanoparticles were characterized by FT-IR spectroscopy. The luminescence of silicon colloid was observed in the wide range between 340 nm and near 700 nm and showed white color with commercial low-intensity UV-Iamp exposure. This synthetic strategy is potentially applicable for illuminating devices such as white light emitting diodes.
Keywords: POROUS SILICON; NANOPARTICLES; LUMINESCENCE